Post-conflict Reconciliation in Aceh, Indonesia: Perspectives from the Victims - Abdul Manan; Abdul Hadi; Iping Rahmat Saputra (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
This field research using participant observation critically analyzed the post-war reconciliation between Aceh Province and the Indonesian Government. Special attention was paid to the violent incidents at Rumoh Geudong, Krueng Arakundoe, and Jambo Keupok. Besides, in-depth interviews with 16 informants who were engaged directly and indirectly on the problems to collect the data, followed by employing library research to sight the findings. The peace agreement was concluded by parties who hated each other. Contrarily, the government’s function as the developer of the post-understanding process was not shown substantially. This has further enhanced the new forms of violence carried out after the previous violence. This meant nothing to the power of peace itself. The reconciliation was not substantially successful but failed. The absence of which had an impact on the existence of war victims, particularly in rebuilding their psychological conditions. Human values during the 14 years of peace were not programmed in priority at all, which generated extensive sustainable peace. The collapse of the state’s responsibility to unravel all cases of dehumanization had an impact on the increasingly dominating pragmatic value, meaning that the value of the existence of war victims was minimal, even closer to nothing.